Pengendalian Rayap Tanah Coptotermes curvignathus Holmgren Menggunakan Ekstrak Daun Gulma Sembung Rambat (Mikania micrantha Kunth) - Farah Diba, Devi Mulia Salam, Mukarlina, (Jurnal Protobiont, 2014)
Mile-a-minute weeds (Mikania micrantha Kunth) contain secondary metabolite compounds such as tannins, alkaloids, saponins, steroids and terpenoids that can be used as insecticides. Those compounds can be used to regulate subterranean termites Coptotermes curvignathus Holmgren. This study aims to find Lethal Concentration (LC)50 extract of M. micrantha on C. curvignathus and extract concentration of M. micrantha which caused least weight loss percentage of paper disc. The research was conducted in 3 months at the laboratory of Biotechnology in Faculty of Mathematics and Science of Tanjungpura University and laboratory of Forest Product Technology in Faculty of Forestry of Tanjungpura University. Extract of M. micrantha was obtained through maseration method using methanol. The no-choice bioassay test was carried-out by treating paper discs with extracts at the concentration of 6%, 8%, 10% w/v (g/ml), DMSO 10% as control solvent and termiticide (has active compounds fipronil 50 g/l) was made at the concentration of 5% v/v (ml/ml) as positive control. LC50 determined by probit analysis. The bioassay test showed that LC50 extract of M. micrantha has an effect to C. curvignathus in 8,07%, and caused least weight loss percentage of paper disc (27,26%) in 10%.